The sources’ buildings and their implications in explaining the maqsurah of Ibn Duraid al-Tabrizi (d. 502 AH - Al-Tamimi, Khamis Abdullah (Al-Adab Journal, 2015)
The research tackles one of the morphological topics entitled “ the structure and semantics of the Infinitival Patterns in the explanation of Ibn Duraid Maqswra for Al-Tabrizi (dead 502 H), the Infinitival Patterns in Arabic, is the base action out of time, person and place outside the relations of the context, the study has reveled Al-Tabrizi care for morphological researches in his general explanation for the verses of his Maqswra, and the structure and semantics of bases specifically, after investigation it was clear that the explainer has mentioned previously a number of Infinitival Patterns for the base trilateral verbs, and doubly trilateral verbs, and what is more than trilateral. The morphological structure that AlTabrizi mentioned have come in different forms, different sections and that the Infinitival Patterns of the trilateral verb are the most common compared to the other Infinitival Patterns structures that have been mentioned in his explanation of the Maqswra , which this study revealed.